2017
DOI: 10.1111/jpn.12679
|View full text |Cite
|
Sign up to set email alerts
|

Arginine for gestating sows and foetal development: A systematic review

Abstract: SummaryThe use of functional amino acids during pregnancy has been linked to improved reproduction in mammals. In this context, arginine is a precursor in the synthesis of numerous molecules, such as nitric oxide and polyamines, which play an important role during reproduction. However, contradictory studies are found in the literature, particularly regarding the amount of supplementation and the period of pregnancy in which it is used. The objective of this study was to evaluate the effects of dietary arginin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…The general information about the articles selected for each database is presented in Tables 1 and 2 As part of the methodology of the systematic review, quality criteria that allowed the characterization of articles for precision in the methodology were employed (Table 3), assuring the reliability of the results (Palencia et al, 2017). The final objective of this evaluation was to note and discuss some relevant aspects of experimentation to improve methods and protocols used in the development of research projects.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The general information about the articles selected for each database is presented in Tables 1 and 2 As part of the methodology of the systematic review, quality criteria that allowed the characterization of articles for precision in the methodology were employed (Table 3), assuring the reliability of the results (Palencia et al, 2017). The final objective of this evaluation was to note and discuss some relevant aspects of experimentation to improve methods and protocols used in the development of research projects.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The decreased values for within‐litter standard deviation and within‐litter coefficient of variation of piglet birthweights highlight the potential of L‐arginine supplementation to improve litter uniformity and lower the incidence of piglets with low viability (Madsen, Pardo, Kreuzer, & Bee, ; Palencia et al, ; Shi et al, ). Quesnel et al () observed a decreased coefficient of variation and improved uniformity in piglet birthweights after L‐arginine supplementation during the final third of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Piglet birthweight is thought to be directly related to piglet survival (Quiniou et al, 2002;Roehe & Kalm, 2000). The effect of L-arginine supplementation on piglet birthweight remains unclear, and the literature presents conflicting results (Palencia et al, 2017). L-arginine supplementation at 0.5% in the last third of gestation increased piglet birthweights by approximately 100 g, thus suggesting increased placental blood flow and improved foetal development compared with non-supplemented sows (Nuntapaitoon, Muns, Theil, & Tummaruk, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a study by Li et al. () detected reduced embryonic survival and plasma progesterone in sows during gestation at diets containing a total of 1.5% arginine in the diet (0.8% of which was supplemented), other authors reported beneficial effects on embryonic/foetal survival in sows and survival of offspring with diets containing up to a total of 1.7% arginine in the diet (up to 1% of which was supplemented) (Mateo et al., , ; Li et al., ; Palencia et al., ). The FEEDAP Panel notes that this literature review, while providing some additional information, does not modify the previous assessments concerning arginine supplementation in target species (EFSA, ; EFSA FEEDAP Panel, , ).…”
Section: Assessmentmentioning
confidence: 99%